2014
DOI: 10.1016/j.ijscr.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Associating liver partition and portal vein ligation for a patient with hepatocellular carcinoma with a background of hepatitis B related fibrotic liver

Abstract: HighlightsAssociating liver partition and portal vein ligation for staged hepatectomy (ALPPS) has rarely been reported for patients with hepatocellular carcinoma (HCC).ALPPS is feasible even in the context of HCC with a background of chronic hepatitis B related liver fibrosis.The hypertrophy rate of the liver remnant was slower and the time needed between the two stages of the operation was longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Previous reports suggest that careful patient selection for ISLT is necessary to reduce the mortality [6,35,36]. The advantage of ISLT strategies is clearly seen in the high proliferative stimulus that induces hypertrophy of the FLRV at a rate that is unmatched by PVE [17,[37][38][39]. An inadequate increase in the FLRV after PVE is a challenging and limiting problem which represents an exclusion criteria for extended hepatic resection [2,3,34,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that careful patient selection for ISLT is necessary to reduce the mortality [6,35,36]. The advantage of ISLT strategies is clearly seen in the high proliferative stimulus that induces hypertrophy of the FLRV at a rate that is unmatched by PVE [17,[37][38][39]. An inadequate increase in the FLRV after PVE is a challenging and limiting problem which represents an exclusion criteria for extended hepatic resection [2,3,34,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, insufficient regeneration is accompanied by chronic liver disease. Chia et al reported that patients with hepatitis B virus (HBV)-related cirrhosis require a longer time for regeneration before stage 2 [ 25 ]. Furthermore, neoadjuvant chemotherapy and chemotherapy have been reported to inhibit liver regeneration to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The short-and long-term effects on biological behavior of tumor growth is still unclear. Although there is a clinical report suggesting that ALPPS is also feasible in liver fibrosis 28 , there is no solid data to support its use in liver fibrosis. The procedure still needs further clinical data, and more basic researches are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…The associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) procedure is a new surgical strategy. It represents a modification of a two-stage hepatectomy in which complete parenchymal transection is associated with ligation of contralateral portal vein 7 8 . It produces a significant increase of the FLR in a much shorter time compared with PVL or PVE.…”
mentioning
confidence: 99%